2017
DOI: 10.1007/s11910-017-0785-3
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Complications of Therapeutic Monoclonal Antibodies: Trends from Oncology to Rheumatology

Abstract: The number of commercially available, evidence-based therapeutic monoclonal antibodies continues to expand. In oncology, immune checkpoint inhibitors are particularly important, as a wide range of central and peripheral nervous system complications are described. In rheumatology, anti-TNF alpha drugs remain associated with demyelinating syndromes. The number of therapeutic monoclonal antibodies encountered in practice continues to grow, as does the number of described neurological complications. Recognition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 137 publications
0
22
0
1
Order By: Relevance
“…Central inflammation is rare and includes, in addition to typical demyelination, several antibodymediated and paraneoplastic conditions such as anti-NMDA receptor encephalitis. 10 A recent review 11 on irAEs and neurotoxicity including 29 articles encompassing 38 patients identified 11 patients with CNS toxicity. TM has only been reported in 5 cases so far (table e-1, links.lww.com/NXI/A268).…”
Section: Discussionmentioning
confidence: 99%
“…Central inflammation is rare and includes, in addition to typical demyelination, several antibodymediated and paraneoplastic conditions such as anti-NMDA receptor encephalitis. 10 A recent review 11 on irAEs and neurotoxicity including 29 articles encompassing 38 patients identified 11 patients with CNS toxicity. TM has only been reported in 5 cases so far (table e-1, links.lww.com/NXI/A268).…”
Section: Discussionmentioning
confidence: 99%
“…He was treated with IVIG plus concurrent steroids for a coexisting pembrolizumab‐associated autoimmune hepatitis. Furthermore, numerous cases of encephalitis and myasthenia gravis have been reported as well as a case of motor polyradiculopathy, 1 case of chronic inflammatory demyelinating polyradiculopathy, and 1 case of necrotizing myositis of the diaphragm …”
Section: Discussionmentioning
confidence: 99%
“…Применение ВВИГ (в том числе вместе с МКА к ИЛ-6/ siltuximab) в таких случаях преследует цели блокирования/ослабления «цитокинового шторма», вызванного гиперактивацией клеток под действием МКА, профилактику последствий гипогаммаглобулинэмии, вызванной терапевтическими МКА к В клеткам [33]. Вызванная введением СD19-или CD22-специфических ХАРТ/CART клеток (Т клеток с химерным антиген-специфическим рецептором) или СD20-специфических МКА (ритуксимаб) гипогаммаглобалинэмия (IgG = 4,0 -6, 0 г/л) требует введения ВВИГ каждые 3-4 недели для профилактики бронхитов, синуситов, пневмоний, энтеровирусных менингоэнцефалита [34][35][36]. В случае применения МКА к фактору некроза опухолей-альфа, широко используемых в ревматологии, нередко встречаются неврологические демиелинизирующие осложнения, которые хорошо купируются введением ВВИГ (2 г/кг веса в течение 5 дней) [16,34].…”
Section: другие хорошо известные синдромы с иммунодефицитомunclassified